Star Up Ecopreneur for Students with Special Needs Through Waste Bank Based on Digital Record - Wijiastuti, Asri; Masitoh, Siti; Ardianingsih, Febrita; Andajani, Sri Joeda (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2021)
The Corona virus pandemic has forced the Indonesian people to adapt their lifestyle by conducting online transactions. Changes in people's lifestyles have an impact on increasing the use of plastic waste , so as not to cause pollution due to the burning of plastic waste that causes carcinogens, must find a solution by managing it from the source. The objective of Community Service activities is To increase knowledge and skills of children with special needs in sorting waste, determining selling prices, recording customer data, transactions with waste collector, recording in savings borrowing and saving mechanisms in the implementation of waste banks based. This activity was carried out using the one shoot case study method, respondents were given an intervention to know computers, recognize selling waste, record transactions digitally, then given a test. The results of the activity show that children with hearing impairments are able to follow and recognize computers, only recording using the excel program still requires further assistance. Knowledge related to types and selling prices to waste collector requires mentoring from teachers. The conclusion is that the waste bank is an alternative to build ecopreneurs and environmental awareness for children with special needs.